Imersão virtual no movimento de mulheres das ilhas de Belém, Pará, Brasil - GUERRA, Gutemberg Armando Diniz (Universidade Federal do Pará, 2021)
The aim of this article is to describe the methodological process of monitoring the Belem Islands Women's Movement - MMIB, originally from May 24 to December 30, 2016, and later with updates until 2019, through the group of WhatsApp created by the leaderships, and other virtual instruments that served as source of information for the elaboration of a Master's thesis. As one of the communication tools among the members of the organization was WhatsApp, it was requested that researchers could be allowed to join the group, since it would allow them to be aware of all their activities. Besides the virtual communication, frequent visits were made throughout the year 2016, particularly during collaborative efforts (grouping), meetings, project activities, festive activities and visits for interviews with members of the organization. It is concluded by the enormous importance of this daily means of communication that allows a visualization of the relationship between group members and their sympathizers, performing as an element of utility with wide possibilities of communication, registration and immersion in the research environment.